Negative Effects of Chronic Rapamycin Treatment on Behavior in a Mouse Model of Fragile X Syndrome - Saré, Rachel M.; Song, Alex; Loutaev, Inna; Cook, Anna; Maita, Isabella; Lemons, Abigail; Sheeler, Carrie; Smith, Carolyn B. (Frontiers in Molecular Neuroscience, 2018)
Fragile X syndrome (FXS), the most common form of inherited intellectual disability, is also highly associated with autism spectrum disorders (ASD). It is caused by expansion of a CGG repeat sequence on the X chromosome resulting in silencing of the FMR1 gene. This is modeled in the mouse by deletion of Fmr1 (Fmr1 KO). Fmr1 KO mice recapitulate many of the behavioral features of the disorder including seizure susceptibility, hyperactivity, impaired social behavior, sleep problems, and learning and memory deficits. The mammalian target of rapamycin pathway (mTORC1) is upregulated in Fmr1 KO mice and is thought to be important for the pathogenesis of this disorder. We treated Fmr1 KO mice chronically with an mTORC1 inhibitor, rapamycin, to determine if rapamycin treatment could reverse behavioral phenotypes. We performed open field, zero maze, social behavior, sleep, passive avoidance, and audiogenic seizure testing. We found that p-S6 was upregulated in Fmr1 KO mice and normalized by rapamycin treatment, but, except for an anxiogenic effect, it did not reverse any of the behavioral phenotypes examined. In fact, rapamycin treatment had an adverse effect on sleep and social behavior in both control and Fmr1 KO mice. These results suggest that targeting the mTOR pathway in FXS is not a good treatment strategy and that other pathways should be considered.